Respuesta :

The answer is approximately -0.112

:)))

Answer:

The quotient is 2-√3-2√2+√6/-2

Step-by-step explanation:

To find the quotient of the surd

2-√8/4+√12 we will rationalize the surdic equation and this is done by multiplying the equation through with the conjugate of the denominator 4-√12 to have;

2-√8/4+√12 × 4-√12/4-√12

= (2-√8)(4-√12)/(4+√12)(4-√12)

= 8-2√12-4√8+√96/8-12

= 8-2√(3x4)-4√(2×4)+√(16×6)/-8

= 8-4√3-8√2+4√6/-8

4(2-√3-2√2+√6)/-8

(2-√3-2√2+√6)/-2

The quotient is therefore

2-√3-2√2+√6/-2

ACCESS MORE